2010
DOI: 10.1111/j.1532-7795.2009.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

A Reinterpretation of Parental Monitoring in Longitudinal Perspective

Abstract: A commonly used measure of parental monitoring is parents' knowledge of adolescents' daily activities. This measure has been criticized on the grounds that parents get more knowledge about teenagers' daily activities through willing youth disclosure than through their own active monitoring efforts, but this claim was based on cross‐sectional data. In the present study, we reexamine this claim with longitudinal data over 2 years from 938 seventh and eighth graders and their parents. Youth disclosure was a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
602
7
26

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 525 publications
(683 citation statements)
references
References 41 publications
48
602
7
26
Order By: Relevance
“…A longitudinal Dutch study found a reciprocal relationship between parental solicitation for information and adolescents' disclosure, whereby both constructs positively predicted each other over time (Keijsers et al 2010). However, the study by Kerr et al (2010) did not find a causal relationship between parental monitoring and youth disclosure.…”
Section: Parental Knowledge Of Children's Offline Behaviormentioning
confidence: 80%
See 1 more Smart Citation
“…A longitudinal Dutch study found a reciprocal relationship between parental solicitation for information and adolescents' disclosure, whereby both constructs positively predicted each other over time (Keijsers et al 2010). However, the study by Kerr et al (2010) did not find a causal relationship between parental monitoring and youth disclosure.…”
Section: Parental Knowledge Of Children's Offline Behaviormentioning
confidence: 80%
“…There is no consensus, however, about the relative importance of these respective knowledge-generating activities. A longitudinal study found that child disclosure predicts parental knowledge about daily activities and whereabouts while active parental monitoring efforts did not (Kerr et al 2010). Another longitudinal study found that child disclosure and active parental monitoring both constitute parental knowledge (Lippold et al 2014a).…”
Section: Parental Knowledge Of Children's Offline Behaviormentioning
confidence: 99%
“…Recent longitudinal research provides evidence of an effect in this direction. Specifically, some (e.g., Keijsers, Branje, Frijns, Finkenauer, & Meeus, 2010;Willoughby & Hamza, 2010), but not all (Kerr, Stattin, & Burk, 2010) studies have found that parents' solicitation predicts more subsequent disclosure by adolescents. Additionally, shared family activities and parental active involvement in adolescent activities also have been found to precede more subsequent disclosure (Willoughby & Hamza, 2010).…”
Section: Bidirectional Links Between Parental Monitoring and Adolescementioning
confidence: 99%
“…This measure covers mother-adolescent agreement in the domains of school and leisure activities. Using this measure in longitudinal research revealed a decrease in children's disclosure over a two years period, most likely because adolescents are granted more freedom and autonomy from parents (Kerr et al 2010). In sum, parental knowledge is mainly gained from their offspring's disclosure, but it remains unclear whether mothers and adolescents would agree on the amount of information adolescents disclose to their parents.…”
Section: Mother-adolescent Agreement On Child Disclosurementioning
confidence: 99%
“…For many decades, researchers assumed that parental knowledge was based on parents' controlling their children and thus the term "monitoring" was used to describe parental knowledge. Recent evidence suggests, however, that parents in fact acquire their knowledge through their children's voluntary disclosure Kerr et al 2010). High levels of children's disclosure represent a form of parent-child communication characterized by children voluntarily sharing information with their parents, and is assumed to be the result of adolescents' "trust in their parents -whether they feel that their parents are willing to listen to them, are responsive, and would not ridicule or punish if they confided in them" Kerr 2000, p. 1083).…”
Section: Mother-adolescent Agreement On Child Disclosurementioning
confidence: 99%